ПОМОГИТЕ ПОЖАЛУЙСТА!!!! Упростите выражение: а) tg( пи+ α)*ctg( пи- α)+1 б) (tg α+ctg...

0 голосов
37 просмотров

ПОМОГИТЕ ПОЖАЛУЙСТА!!!!
Упростите выражение:

а) tg( пи+ α)*ctg( пи- α)+1
б) (tg α+ctg α)^2 - (tg α-ctg α)^2
в) cos^2 α-1/sin^2α -1 -tg^2 α


Алгебра (19 баллов) | 37 просмотров
Дан 1 ответ
0 голосов

A) tg(π+α)*ctg(π-α)+1=tgα*(-ctgα)+1= -tgα*ctgα+1= -1+1=0

б) (tgα+ctgα)² - (tgα-ctgα)²=
    =(tgα+ctgα-tgα+ctgα)(tgα+ctgα+tgα-ctgα)=
    =2ctgα * 2tgα=4tgα*ctgα=4*1=4

в)
\frac{cos^2 \alpha -1}{sin^2 \alpha -1}-tg^2 \alpha = \frac{-sin^2 \alpha }{-cos^2 \alpha }-tg^2 \alpha =tg^2 \alpha -tg^2 \alpha =0


(233k баллов)